Inventing subjects studies in hegemony, patriarchy, and colonialism - Bannerji Himani (New Delhi Tulika, 2001)
Articles on the socio-cultural identity of women in West Bengal, India.
Keywords: Women -- India -- West Bengal -- Social conditions -- 19th century; Women -- India -- West Bengal -- Social conditions -- 20th century; West Bengal (India) -- Social conditions -- 19th century; West Bengal (India) -- Social conditions -- 20th century